Excess emissions from idling vehicles in Comalcalco, Tabasco - Pérez-Márquez, Fernando (2025)
Motor vehicles have become instruments of great importance for the development of human activities. The objective was to estimate greenhouse gases produced in excess by light vehicles in idling conditions in the Municipality of Comalcalco, Tabasco. From August 30 to December 6, 2023, 471 data were collected from vehicles in idling conditions equal to or greater than one minute in the municipality mentioned above. It was determined that there is an idle time in excess of 1058.4 min, which produces a minimum of 25.9 kg of CO2, 9.3 g of CH4 and 3 g of N2O. In terms of CO2 emission, at least 1,114.8 kg CO2e could be emitted daily from the idling operation of the 20,277 motor vehicles registered in the Municipality until December 2016. Annually, this is equivalent to a generation of 406,982 tons of CO2e due to the consumption of 166,249.87 liters of fuel.